Pengaruh Kompetensi dan Kepemimpinan Transaksional terhadap Kepuasan dan Kinerja Awak Kapal di Miclyn Express Offshore Pte.Ltd - Yan Supriyadi; Retno Anggoro (SAINTARA, 2022)
There are many factors that influence the related problems faced in the field with the level of competence and transactional leadership style. These various factors affect the job satisfaction and performance of crew members at Miclyn Express Offshore, Pte., Ltd. This research was conducted using a verification study model with quantitative data. Verificative research was conducted to test the theory and the results of previous studies. Respondents in the research conducted were crew members of the Miclyn Express Offshore, Pte., Ltd. company which is abbreviated as MEO. MEO company is a company engaged in the transportation sector operating Anchor Handling Tug Supplay (AHTS). Data analysis was carried out by conducting validity tests, reliability tests, normality tests and Sobel tests. The conclusion of this study is that the competence of the crew has a positive and significant effect on the job satisfaction of the crew at Miclyn Express Ofshore, Pte., Ltd. The higher the competence possessed by the crew, the higher the satisfaction felt by the crew when working at Miclyn Express Offshore, Pte., Ltd. The transactional leadership style has a positive and significant effect on the performance of the crew at Miclyn Express Offshore, Pte., Ltd. . Transactional leadership has a positive contribution to improving the performance of the crew, so that with the increase in transactional performance implemented, the performance of the crew of Miclyn Express Offshore, Pte., Ltd and there is an effect of mediation or intervention from transactional leadership and crew on the performance of the crew through job satisfaction. crew at Miclyn Express Offshore,Pte.,Ltd. work objectives are able to increase the contribution of transactional leadership and ship strength to ship performance at Miclyn Express Offshore, Pte., Ltd.